CAN FULL OUTLINE OF UNRESPONSIVENESS SCORE (FOUR) REPLACE GLASGOW COMA SCALE (GCS) IN HEAD INJURY?: VALIDATION AT TERITIARY CARE CENTRE IN NEPAL - Kafle, Prakash; Sharma, Mohan Raj; Shilpakar, Sushil K; Sedain, Gopal; Pradhanang, Amit; Shrestha, Ram Kumar; Rajbhandari, Binod (Journal of Universal College of Medical Sciences, 2018)
Introduction : Traumatic brain injury (TBI) is one of the major cause of severe disability and death world wide.The mortality rate in these patients largely depends on initial severity of trauma. In TBI, initial level of consciousness is most important prognostic indicator. The commonest scale is the Glasgow Coma Scale (GCS). Despite its widespread use, the GCS has some significant limitations, including variations in inter rater reliability and predictive validity. In order to overcome deficiencies of the GCS, an alternative scale called FOUR (Full Outline of Unresponsiveness score) has been developed and validated in several neurosurgical centers in North America. This study was an attempt to validate this score in Nepalese Setting. This study was carried out in the Department of Neurosurgery at Tribhuvan University Teaching Hospital, Kathmandu, Nepal. The main objective ofthe study was to compare the FOUR with GCS in predicting outcome in patients with Traumatic brain injury. MATERIAL AND METHODS: Patients with moderate to severe head injury aged 2: 16 years admitted in the Department ofNeurosurgery were eligible to participate in the study.The GCS and FOUR score were measured at the earliest possible time during admission by the single observer. Glasgow Outcome Scale (GOS) was measured at discharge and at 3 months follow up. Mortality was used as the primary outcome measure. RESULTS: Total of 122 patients were included in the study. The mean age of the study population was 38.7 ± 18 years. Mean GCS score among survivors was higher than that among non-survivors which was statistically significant (10.9 ± 2 vs. 6 ± 1.12 (p <0.001). Similarly mean FOUR score among survivors was significantly higher than that among non-survivors ( 12. 8±2.49 vs. 6.08 ± 1.72 (p< 0.001). The cut off point for GCS and FOUR score were ≤ 7and ≤ 8 respectively. The area under ROC curve for GCS for prediction of mortality was 0.975 (95% CI; 0.947-1.000; p<0.001) and for FOUR score was 0.981 (95% CI; 0.960-1.000; p<0.001) suggesting good discrimination ability ofboth models.The overall sensitivity, specificity, positive predictive value and negative predictive values of GCS were 91.67%, 91.82%, 55% and 99% respectively while that for FOUR score were 100%, 91.82%, 57.1 % and 100%respectively. CONCLUSION: The outcome measurement of FOUR score was comparable with the GCS in traumatic brain injury and both the scores correlated well. Journal of Universal College of Medical Sciences Vol. 6, No. 1, 2018, Page: 32-39